1994
DOI: 10.1007/bf01830243
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposures as risk factors for gastric cancer in Italy

Abstract: Occupational associations with gastric cancer were investigated in a multicenter case-control study in Italy involving interviews with 640 histologically confirmed male cases and 959 controls, randomly selected from the resident populations of the study areas. From information on the three jobs each person held the longest, risks were evaluated according to employment in 35 occupations (ever or 21+ years) and to estimated exposure (ever or 21+ years) to six chemicals using a job-exposure matrix. All risk estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 42 publications
(8 reference statements)
3
34
0
Order By: Relevance
“…In a recent Norwegian study, a possibly increased risk of gastric cancer was found among lighthouse keepers who drank water highly contaminated with asbestos, 55 and similar weak positive associations with gastric cancer have been reported from other studies of workers exposed to asbestos. [56][57][58][59][60] In other investigations, however, no such association has been found. 35,[61][62][63] The lack of association between exposure to asbestos and risk of gastric cancer in our study further argues against influence of airborne asbestos in the etiology of gastric cancer.…”
Section: Discussionmentioning
confidence: 78%
“…In a recent Norwegian study, a possibly increased risk of gastric cancer was found among lighthouse keepers who drank water highly contaminated with asbestos, 55 and similar weak positive associations with gastric cancer have been reported from other studies of workers exposed to asbestos. [56][57][58][59][60] In other investigations, however, no such association has been found. 35,[61][62][63] The lack of association between exposure to asbestos and risk of gastric cancer in our study further argues against influence of airborne asbestos in the etiology of gastric cancer.…”
Section: Discussionmentioning
confidence: 78%
“…In case of gastric cancer, we included farming work that involved exposure to herbicides (116) and also grain and animal dust as a risk factor. A dusty work environment in many other occupations has been linked with a risk of gastric cancer (117,118). The Montreal study (113) also reported an elevated risk of gastric cancer for specific workplace dusts (grain dust, lead dust, and zinc dust).…”
Section: Criteria Used For Selecting the Studiesmentioning
confidence: 99%
“…Low social class and unhealthy dietary habits are the main risk factors for stomach cancer, with occupational factors playing a minor role, if any (27). Farmers have been considered at risk, and a role of pesticide exposure has been postulated (27)(28)(29). However, no specific agricultural exposure has been identified and the rural association may have resulted from confounding by lifestyle habits associated with rural residence (29).…”
Section: Discussionmentioning
confidence: 99%
“…Farmers have been considered at risk, and a role of pesticide exposure has been postulated (27)(28)(29). However, no specific agricultural exposure has been identified and the rural association may have resulted from confounding by lifestyle habits associated with rural residence (29). We adjusted for ethnicity to partially control for differences in education and dietary habits between the unexposed, who more frequently were from non-Sardinian origin, and the exposed subcohorts.…”
Section: Discussionmentioning
confidence: 99%